Untersuchung und Modellierung des Haltezeiteinflusses auf die zyklische Entfestigung ferritisch-martensitischer Stähle - Führer, Ulrich (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2021)
Ferritic-martensitic steels are established structural materials for high-temperature applications. However, these steels show characteristic softening under cyclic loading. Based on a comprehensive mechanical characterization, a coupled viscoplastic model was established to describe cyclic softening and lifetime of ferritic-martensitic steels under combined creep-fatigue loading.